Sales Growth Memoderasi Transfer Pricing, Thin Capitalization, Profitabilitas, dan Bonus Plan Terhadap Tax Avoidance Practice - Suryantari, Ni Putu Lissya; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 32 No 4 (2022)DO - 10.24843/EJA.2022.v32.i04.p01, 2022)
The study was conducted to obtain empirical evidence testing the moderating effect of sales growth on the effect of transfer pricing, thin capitalization, profitability and bonus plans on tax avoidance. Tax avoidance is a tax planning practice to reduce the company's tax burden by taking advantage of imperfections in the law. The research population is multinational companies in the manufacturing sector which are listed on the Indonesia Stock Exchange in 2016-2020. The data analysis technique used is Moderated Regression Analysis (MRA). The results of the analysis provide evidence that thin capitalization and profitability have a positive effect on tax avoidance, while transfer pricing and bonus plans have no effect on tax avoidance, then sales growth is able to weaken the effect of thin capitalization, profitability and bonus plans but is unable to weaken the effect of transfer pricing on tax avoidance. Keywords: Tax Avoidance; Transfer Pricing; Thin Capitalization; Profitability; Bonus Plans; Sales Growth.